Analsisis Face Validity dan Content Validity Tes Bahasa Inggris: Sebuah Open Lesson dalam Lesson Study for Learning Community - Muh Syafei (Universitas Muria Kudus, 2018)
This paper presents Open Lesson activities in a series of Lesson Study for Learning Community (LSLC) activities in the Language Assessment (LA) course that is taught by the author with partners from other lecturers in the same subject. In this open lesson the theme raised is the material